From Resources to Industrial Dominance: Structural Transformation and Sectoral Imbalance in Morowali Regency - Muh Fardan Ngoyo; Dirmansyah Darwin; I Made Jyotisa Adi Dwipatna (CV. ULIL ALBAB CORP, 2026)
This study examines the trajectory of structural transformation in Morowali Regency over the period 2005–2025, focusing on how the transition from the primary to the secondary sector occurred. Drawing from a quantitative descriptive approach using secondary data on gross regional domestic product (GRDP) of Morowali Regency and Central Sulawesi, this study analyzes sectoral dynamics through changes in the contributions of the primary, secondary, and tertiary sectors over time, examined by Location Quotient (LQ) analysis to identify base and non-base sectors. The results indicate a significant shift away from the dominance of the primary sector toward the secondary sector, particularly through industrial expansion in resource-based manufacturing. However, this transformation exhibits characteristics of uneven structural change, where manufacturing sector remains highly concentrated which accounted for 79 percent from total GRDP and 1,78 of LQ score in 2025, where is not fully accompanied by broad-based diversification or strong inter-sectoral linkages. These findings suggest the need for policies that promote economic diversification and enhance sectoral linkages to ensure more inclusive and sustainable regional economic development. This study contributes to the literature by providing a long-term, region-specific analysis of structural transformation in a resource-rich economy, highlighting the tension between rapid industrialization and sustainable development pathways in emerging regions